Rancang Bangun Mesin Pembuat Minuman Kopi Otomatis Berbasis Arduino UNO dengan Kontrol Android - Nini Firmawati; Gentha Farokhi; Wildian Wildian (JITCE (Journal of Information Technology and Computer Engineering), 2019)
Design of automatic coffee drink maker machine based on arduino uno has been successfully done. Coffee drink maker machine system consists of four parts, namely the selection of the menu of coffee drinks, detection of coffee cups, pouring coffee, sugar and cream and pouring water. The selection of coffee drinks menu is done through applications on android smartphone which is connected to the engine via a bluetooth module HC-06. Detection of cup using the censor of photodiodes. Coffee, sugar, and cream is poured and measured using solenoid doorlock. For pouring water using velve selenoid. There are three menu choices on a machine that are bitter coffee, sweet coffee, and cream coffee. For the production of bitter coffee drinks solenoid doorlock pouring coffee an average 5.03 grams in 3 seconds. For the production of sweet coffee drinks solonoid doorlock coffee pouring an average 5.33 grams sugar and pouring an average 17.50 grams within 8 seconds. For the production of coffee cream solenoid doorlock pouring coffee an average 5.27 grams, pouring sugar an average 17.46 grams and pouring cream an average 5.42 grams within 11 seconds. For pouring water using velve solonoid and stops automatically when the distance between the sensor and the surface of the ultrasonic water reaches 5 cm by the time pouring over the last 13 seconds.